2014
DOI: 10.1063/1.4862859
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman scattering in bulk 2H-MX2 (M = Mo, W; X = S, Se) and monolayer MoS2

Abstract: We have performed a comparative study of resonance Raman scattering in transition-metal dichalcogenides 2H-MX 2 semiconductors (M ¼ Mo, W; X ¼ S, Se) and single-layer MoS 2. Raman spectra were collected using excitation wavelengths 633 nm (1.96 eV), 594 nm (2.09 eV), 532 nm (2.33 eV), 514 nm (2.41 eV), and 488 nm (2.54 eV). In bulk-MoS 2 and WS 2 , the resonant energies appear to coincide with their exciton excitations. The resonance can be fine tuned by varying sample temperatures, which confirms its excitoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 62 publications
7
86
0
Order By: Relevance
“…The resonance Raman spectra show that multiple modes are shifted from the first-order Raman frequencies, which suggests that the electronic transitions are strongly coupled with phonon modes. There are several reports of this resonant Raman scattering phenomenon in MoS2 [78,79,86,91,93,[98][99][100]. All of these studies are in general agreement on the attribution of the peaks observed in the resonant Raman scattering spectrum, which suggests coupling between vibrational modes and longitudinal acoustic phonon modes.…”
Section: Resonant Raman Scatteringsupporting
confidence: 69%
See 2 more Smart Citations
“…The resonance Raman spectra show that multiple modes are shifted from the first-order Raman frequencies, which suggests that the electronic transitions are strongly coupled with phonon modes. There are several reports of this resonant Raman scattering phenomenon in MoS2 [78,79,86,91,93,[98][99][100]. All of these studies are in general agreement on the attribution of the peaks observed in the resonant Raman scattering spectrum, which suggests coupling between vibrational modes and longitudinal acoustic phonon modes.…”
Section: Resonant Raman Scatteringsupporting
confidence: 69%
“…Finally, the intensity of resonance Raman modes have an observed temperature dependence in some studies [85,[98][99][100]106]. For example, J. M. Chen and C. S. Wang had detected both the dependence of the second-order Raman modes at room temperature (300K) and liquid nitrogen temperature (80K).…”
Section: Resonant Raman Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the resonant excitation energy will be different because of the different band structures. For example, Fan et al found that the Raman resonance in bulk WS 2 covers a large energy range from 1.96 (633 nm) to 2.41 (514 nm) eV, 101 which is attributed to the broad features of its B exciton (Fig. S4, ESI).…”
mentioning
confidence: 99%
“…The Fabry-Perot (FP) cavity can be tuned for the used wavelength to enhance different optical effects in a single layer, from visualization 13 by color contrast 14 to observation of luminescence 1 and Raman scattering. 15,16 In order to get quantitative information from such measurements, direct calculations of transmissivity and reflectivity with interference taken into account are required.…”
Section: Introductionmentioning
confidence: 99%